Hybrid Thermo-Responsive Polymer Systems and Their Biomedical Applications - Sarwan, Taskeen; Kumar, Pradeep; Choonara, Yahya E.; Pillay, Viness (Frontiers in Materials, 2020)
Targeted and controlled drug delivery employing "smart materials" is a widely investigated field, within which stimuli-responsive polymers, particularly those which are thermo-responsive, have received considerable attention. Thermo-responsive polymers have facilitated the formulation of insitu gel forming systems which undergo a sol-gel transition at physiological body temperature, and have revolutionised the fields of tissue engineering, cell encapsulation, and controlled, sustained delivery of both drugs and genes. However, the use of single thermo-responsive polymers in the creation of these systems has posed numerous problems in terms of physico-mechanical properties. Hybridisation of these thermo-responsive polymers has therefore been employed, resulting in the creation of tailor-made drug delivery systems with optimal gelation temperatures and concentrations, ideal viscosities and improved gel strengths. This article reviews various thermo-responsive polymers that have been employed in the formulation of thermo-gelling systems. Special attention has been given to the hybridisation of each of these polymers, the resulting systems that have been created, and their biomedical applications.